Study guides

Q: 9a plus 8 minus 2a minus 3 minus 5a?

Write your answer...

Submit

Related questions

2a+5

2a+5a+9a = 16a

9a +8 -2a -3 -5a = 2a +5

4a2 - 9a + 5 = 4a2 - 4a -5a + 5 = 4a(a - 1) - 5(a - 1) = (4a - 5)(a - 1)

9a + 1

9a + 3b - 11a - 4b = -2a -b

a + 3a + 5a = 180 9a =180 a = 20

It is the same as: 9a -4a = 5a

Collect like terms: 9a -7a = 9 - 15, ie 2a = -6, so a = -3

so 5a = -20 making a = -4

It is: -7a when simplified

In order to solve something, there needs to be an equation. If I have read your equation right you have: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) This looks like it needs to be simplified. There are two fractions being multiplied, so multiply the numerators and denominators together, giving: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) = ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) Now, simplify the polynomials to remove the squared terms and any common factors: a² - 4 = (a - 2)(a + 2) 2 + 6a = 2(1 + 3a) 3 + 9a = 3(1 + 3a) a² + 5a + 6 = (a + 3)(a + 2) Giving: ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) = ((a + 2)(a - 2)3((1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) This can now be simplified by cancelling out equivalent terms, giving: ((a + 2)(a - 2)3(1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) = ((a - 2)3) / (2(a+3)) = 3(a - 2) / 2(a + 3) = (3a - 6) / (2a + 6)

4a - 2.1 = 9a + 5.4 4a - 9a = 5.4 +2.1 -5a = 7.5 -a = 1.5 a = -1.5

(a - 6)(2a + 3)

9a - 8a = a

(9a + 2)(9a + 2)

Because of limitations with the question software, some symbols cannot be rendered, so we don't know what operation there is between the 5a and the 4a-1. Assuming a plus sign produces an inconsistent equation. But if we assume a / (slash) for division, we get a quadratic equation that produces some reasonable roots, so here's what I think the question is: Can you solve the following equation for a: 5a/(4a-1) = 9a-4 ? Yes you can! Multiply both sides of the equation by 4a-1. This gives you: 5a = (9a-4)(4a-1) Expand the right side, which gives you 5a = 36a2 -9a -16a + 4 Subtract 5a from both sides and group similar terms: 0 = 36a2 -30a + 4 Now, use the quadratic formula to solve for a(left to the student): a1 = 2/3; a2 = 1/6

a2+9a+20 = (a+4)(a+5) when factored

Gathering like terms together, this can be rewritten: 9a = 180 Dividing both sides of the equation by 9: a = 20

There is nothing you can do to 9a + 5 without knowing the value of a.

a + b + c = 180 b = 3a c = 5a Substituting the values of b and c into the first equation. a + 3a + 5a = 180 or 9a = 180 so that a = 20 then b = 3a = 3*20 = 60 and c = 5a = 5*20 = 100

-14 + 9a = 389a = 52a = 52/9 or 5.78

9a + 7b *remember to look and understand the letters!*

9a. You take 11 a's: a a a a a a a a a a a and then take away two (minus a, minus a): a a a a a a a a a X X

9a+21 3(3a+7)